2011
DOI: 10.1111/j.1574-6968.2011.02451.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary molecular identification of cylindrospermopsin-producing Cyanobacteria in two Polish lakes (Central Europe)

Abstract: The presence of toxigenic cyanobacteria capable of biosynthesis of cylindrospermopsin (CYN) was measured in 24 water samples collected from the lakes Bytyńskie (BY) and Bnińskie (BN) in the Western Poland. The study also covered analysis of toxigenicity and production of CYN by the culture of Cylindrospermopsis raciborskii isolated from BY. The cyrJ gene associated with CYN production was identified in 22 water samples collected in the summer seasons of 2006 and 2007. The presence of CYN was confirmed in 16 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…Therefore, it is likely that CYN is widely distributed in European waters; however, the list of potential producers of this toxin remains incomplete. Moreover, no CYN-producing strains of C. raciborskii have yet been isolated, although it is a commonly occurring species in this region (Fastner et al 2003, 2007; Saker et al 2003; Bernard et al 2003; Haande et al 2008; Antal et al 2011; Mankiewicz-Boczek et al 2012). In Poland, CYN was first detected in 2006 in two shallow eutrophic lakes (Kokociński et al 2009), and preliminary molecular identification has shown that Aphanizomenon sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is likely that CYN is widely distributed in European waters; however, the list of potential producers of this toxin remains incomplete. Moreover, no CYN-producing strains of C. raciborskii have yet been isolated, although it is a commonly occurring species in this region (Fastner et al 2003, 2007; Saker et al 2003; Bernard et al 2003; Haande et al 2008; Antal et al 2011; Mankiewicz-Boczek et al 2012). In Poland, CYN was first detected in 2006 in two shallow eutrophic lakes (Kokociński et al 2009), and preliminary molecular identification has shown that Aphanizomenon sp.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, CYN was first detected in 2006 in two shallow eutrophic lakes (Kokociński et al 2009), and preliminary molecular identification has shown that Aphanizomenon sp. appears to be the primary cyanobacterial genus responsible for the production of CYN in Polish lakes (Mankiewicz-Boczek et al 2012). Our recent study showed that C. raciborskii and Aphanizomenon spp.…”
Section: Introductionmentioning
confidence: 99%
“…CYN-producing Cylindrospermopsis from Australia and Asia have been reported, whereas Cylindrospermopsis strains isolated from Europe and America are incapable of CYN production (32)(33)(34)(35)(36). However, no conclusion can be drawn about the geographic distribution of the CYN-producing genotype of Cylindrospermopsis before additional samples from each continent are investigated by molecular and chemical methods.…”
mentioning
confidence: 97%
“…aphanizomenoides, and C. raciborskii, in line with our previous findings in Lake Karla . Recently it was shown that Aphanizomenon seems to be the main cyanobacterial genus responsible for the production of CYN in Polish lakes (Mankiewicz-Boczek et al, 2012). Evidences point to Aph.…”
Section: Mc-rrmentioning
confidence: 99%